PELAKSANAAN DIKLAT TEKNIS BERBASIS E-LEARNING DALAM RANGKA PENGEMBANGAN KOMPETENSI ASN PADA BADAN DIKLAT PROVINSI GORONTALO - Ibrahim, Irfan (Komunitas Manajemen Kompetitif, 2022)
There is a need for the Gorontalo Provincial Government for professional apparatus resources, encouraging the implementation of comprehensive ASN competency development. If this need is not met, it will have an impact on ineffective and inefficient local government administration so that it has implications for the low quality of service to the community. The development of ASN competencies to meet 20 JP (Lesson Hours) for each ASN is estimated to cost a budget of Rp. 38,142,000,000. This number comes from the number of ASN Gorontalo Provincial Government as many as 5,868 people multiplied by the technical education and training index (average estimate of Rp. 6,500,000 per participant for 20 JP). Not including the obligation for structural training of Rp. 23,880,000,000 for 796 structural officials (the average education and training index is Rp. 30,000,000 per participant). However, the budget availability for ASN competency development at the Gorontalo Provincial Education and Training Agency in 2019 is only Rp. 4,606,239,035, even for the 2020 budget, there was a decrease of only Rp. 1,335,768,521. Inequality in the availability of this budget will cause the implementation of ASN competency development at the Gorontalo Provincial Education and Training Agency will not be achieved as expected. Therefore, based on this problem, the Gorontalo Provincial Education and Training Agency is looking for a solution by developing low-cost education and training so that it will reduce budget dependence. The results of the implementation of e-learning-based technical training have succeeded in reducing the budget needs of the Education and Training Agency by more than 50%.